Lintasan Belajar Pengelompokan Data Bagi Siswa Kelas I Sekolah Dasar Menggunakan Pendekatan PMRI - Yovita Diva Hapsari; Sarifa Nadia; Eka Zuliana (Universitas Maritim AMNI Semarang, 2024)
Education in elementary schools has the aim of helping students understand problems in everyday life. The national education system states that education aims to develop the potential of students to become human beings who have faith, noble character, health, knowledge and responsibility. In the context of mathematics education, the PMRI (Indonesian Realistic Mathematics Education) approach is used to help students understand mathematical concepts through real experiences and the context of everyday life. The data grouping learning trajectory using the PMRI approach aims to help grade 1 elementary school students understand the concept of data grouping. The use of sorting and choosing props can also improve the learning outcomes of low grade students in sorting and selecting certain objects or concepts. The aim of this research is that it is hoped that students can learn more effectively through direct experience, visualization and physical movements involved in the sorting and choosing process. Data was collected through interviews and tests. Based on the results and discussion of the research that has been conducted, it can be concluded that the design of a data grouping learning trajectory for elementary school students using an Indonesian realistic mathematics education approach is theoretically able to provide a deeper understanding of data grouping for grade I elementary school students. With the principles in PMRI, students are given the opportunity to develop a conceptual understanding of data grouping with the help of the images provided.